2018
DOI: 10.25139/htc.v1i2.1337
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh senam Abdominal Stretching terhadap Efektifitas Penurunan Nyeri Dismenorhea Primer Pada Remaja Putri di MA Al-Amiriyyah Blokagung Tahun 2018

Abstract: Dismenorhea merupakan salah satu masalah ginekologi yang paling umum dialami saat masa remaja, sangat mengganggu aktivitas bahkan seringkali mengharuskan penderita beristirahat dan meninggalkan aktivitasnya. Tujuan penelitian untuk mengetahui pengaruh abdominal stretching terhadap efektifitas penurunan nyeri dismenorhea pada remaja putri. Dalam Penelitian ini merupakan penelitian pre experiment dengan one  group pretest-posttest design. Teknik Pengambilan sampel menggunakan  total  sampling dengan jumlah sampe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
1
0
Order By: Relevance
“…Similarly, the results of research (Ningsih et al, 2018), showed that the intensity of menstrual pain (dysmenorrhea) in 30 staff of PT Willbes Global Subang Regency experienced a change to be lighter after practicing yoga techniques and abdominal stretching exercise.…”
Section: Average Difference In Primary Menstrual Pain Intensity (Dysm...mentioning
confidence: 91%
“…Similarly, the results of research (Ningsih et al, 2018), showed that the intensity of menstrual pain (dysmenorrhea) in 30 staff of PT Willbes Global Subang Regency experienced a change to be lighter after practicing yoga techniques and abdominal stretching exercise.…”
Section: Average Difference In Primary Menstrual Pain Intensity (Dysm...mentioning
confidence: 91%
“…The results of the Central Java Central Statistics Agency Census show that for adolescent girls who experience pain during menstruation as many as 11.78% of the total population of 32,548,687 people, and those experiencing dysmenorrhea there are 1,518,867 people (Ningsih, 2018).…”
mentioning
confidence: 99%